Applied Statistics Module, Version 2: Science, Engineering, Technology - Siti Zanariah, Satari; Noryanti, Muhammad; Siti Roslindar, Yaziz; Nor Hafizah, Moslim; Roslinazairimah, Zakaria; Siti Maznah, Kabeb (Penerbit UMP, 2017)
This module is intended to facilitate teaching and learning of Statistics courses in colleges and universities at degree level. It is specially tailored for students of science, engineering and technology. This book provides examples and exercises that present important ideas of statistics in a realistic setting to show connections between theory and application in industry and scientific research. The materials in this module also integrate well with computer software packages especially in the chapters on descriptive statistics, hypothesis testing, analysis of variance and regression models. The use of Microsoft Excel is emphasised in this module.